2018
DOI: 10.1016/j.jaci.2018.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Specific IgG 4 antibodies to cow's milk proteins in pediatric patients with eosinophilic esophagitis

Abstract: sIgG to CM proteins are common and high titer in children with EoE. Although it is not clear that this response is pathogenic, sIgG levels imply that these antibodies are an important feature of the local immune response that gives rise to EoE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 56 publications
5
59
0
1
Order By: Relevance
“…56 Since then, several studies have confirmed the presence of food-specific IgG4 in the serum. 57,58 In our recent work, the calculated quantitative ratios of IgG4 ab: IgE ab specific to Bos d 4 and Bos d 5 were greater than 1000:1. 58 The implication is that this level of IgG4 can both inhibit IgE assays in vitro and prevent immediate symptoms in vivo.…”
Section: What Role Do Igg and Particularly Igg4 Antibodies Play In Comentioning
confidence: 84%
See 2 more Smart Citations
“…56 Since then, several studies have confirmed the presence of food-specific IgG4 in the serum. 57,58 In our recent work, the calculated quantitative ratios of IgG4 ab: IgE ab specific to Bos d 4 and Bos d 5 were greater than 1000:1. 58 The implication is that this level of IgG4 can both inhibit IgE assays in vitro and prevent immediate symptoms in vivo.…”
Section: What Role Do Igg and Particularly Igg4 Antibodies Play In Comentioning
confidence: 84%
“…57,58 In our recent work, the calculated quantitative ratios of IgG4 ab: IgE ab specific to Bos d 4 and Bos d 5 were greater than 1000:1. 58 The implication is that this level of IgG4 can both inhibit IgE assays in vitro and prevent immediate symptoms in vivo. We have also asked a different question: "What is the normal level of IgG4 to common antigens in the population?"…”
Section: What Role Do Igg and Particularly Igg4 Antibodies Play In Comentioning
confidence: 84%
See 1 more Smart Citation
“…It is unknown whether OIT-associated EoE is due to the unmasking of preexisting, lower-grade esophageal eosinophilia or the initiation of new esophageal disease. Interesting observations have shown that IgG4 levels are increased in EoE (146)(147)(148)(149). IgG4 is thought to be a neutralizing antibody because it binds weakly to activating Fcγ receptors.…”
Section: Oral Immunotherapy and The Mechanism Of Desensitizationmentioning
confidence: 99%
“…The important role of milk as an eliciting food in patients with EoE might be related to the strong anti-milk IgG 4 response, as well as the strong type 2-and regulatory T cell-dependent immunity that are characteristic of EoE. [29][30][31]…”
Section: Eoementioning
confidence: 99%